Dampak Olahraga Berlebihan Terhadap Kualitas Sperma - Mahendra Wahyu Dewangga; Taufiqurrachman Nasihun; Israhnanto Isradji (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Excessive exercise increases the production of Reactive Oxygen Species (ROS) in the body. Too much ROS will result in decreased sperm quality. The purpose of this study was to determine the impact of excessive exercise on sperm quality. The method used was experimental design with post test only control group design on the experimental animal rat Galur Wistar. Rats were given swimming activity for ± 25 minutes every day for 4 weeks. Examination of sperm quality by looking at morphology, motility and sperm count. The results of all examinations obtained a p-value